Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/00140130902767413
|View full text |Cite
|
Sign up to set email alerts
|

Muscular activity and thermal responses in men and women during repetitive work in cold environments

Abstract: Thermal responses and muscular activity in repetitive work were studied in eight women and eight men at 19 degrees C (thermoneutral) and at 4 degrees C (cold). Furthermore, effect of a heating vest was studied at 4 degrees C. Women had lower (p < 0.05) mean skin temperature compared with men at each thermal condition. Muscular activity (microV) was generally higher in women compared with men, being significantly higher in m. deltoideus (p < 0.05). Women had lower (p < 0.01) maximal isometric strength compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Respective values in wrist flexor muscles were 8-12%MEMG, in trapezius 8-14%MEMG, and in shoulder region 6-7%MEMG (Sormunen et al 2006). In a simulated sausage packing work the strain focused on the upper extremity and neck shoulder regions; high values were also found in wrist extensor muscles in females (<20%MEMG) and in males (<16%MEMG) (Sormunen et al 2009). These results are confirmed in the study of Arvidsson et al (2012), where the highest %MEMG values in meat cutters were found in wrist extensor muscles.…”
Section: Food Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Respective values in wrist flexor muscles were 8-12%MEMG, in trapezius 8-14%MEMG, and in shoulder region 6-7%MEMG (Sormunen et al 2006). In a simulated sausage packing work the strain focused on the upper extremity and neck shoulder regions; high values were also found in wrist extensor muscles in females (<20%MEMG) and in males (<16%MEMG) (Sormunen et al 2009). These results are confirmed in the study of Arvidsson et al (2012), where the highest %MEMG values in meat cutters were found in wrist extensor muscles.…”
Section: Food Processingmentioning
confidence: 99%
“…In a cold environment, this translates to greater relative force required to complete a task, or else reduced work capacity or tolerance. Each point represents 8 subjects exceptconditions (Sormunen et al 2009). Higher strain and thus fatigue may be associated to low working temperature, high repetitiveness, awkward postures, and considerable use of force (Christensen et al 2000;McGorry et al 2004;Oksa et al 2002).…”
Section: Food Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…higher in cold conditions 6) and it seems that women are more susceptible to the increased strain than men 8) . In simulated sausage packing work at 4 °C, the average muscular strain for women was 14% of maximal EMG activity (%MEMG), compared with 12%MEMG among men 8) .…”
Section: Introductionmentioning
confidence: 99%
“…In simulated sausage packing work at 4 °C, the average muscular strain for women was 14% of maximal EMG activity (%MEMG), compared with 12%MEMG among men 8) . It has also been found that the level of agonist-antagonist coactivation during low intensity repetitive work or static work increases in cold conditions, thus increasing the strain and fatigue of the working muscles 6,7,9) .…”
Section: Introductionmentioning
confidence: 99%